A modified silicon-carbon negative electrode material and preparation method thereof
Through the combination of modified bitumen and polymer and high-temperature roasting technology, the problem of poor coating uniformity of silicon carbon materials is solved, the capacity and circulation performance of the negative electrode material of lithium-ion battery are improved, and more efficient electrode material preparation is achieved.
Patent Information
- Application Number
- CN202211580546.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-09
AI Technical Summary
The existing lithium-ion battery negative electrode material, silicon carbon material, has poor coating uniformity, particle adhesion agglomeration and asphalt carbonized particles, resulting in low electrode material capacity and low Coulomb efficiency.
After mixing the modifier with asphalt, carbonization is used to form modified asphalt. Combined with linear polysiloxane and fatty alkyl trimethyl halide amine additives, uniformly coated is prepared by high-speed shear dispersion and roasting technology of emulsifier. Si/Gr@C composite material forms a stable core-shell structure.
It improves the capacity and first charge and discharge efficiency of silicon carbon negative electrode materials, enhances the smoothness and circulation performance of particles, reduces the preparation cost, and is suitable for industrial production.
Smart Images

Figure CN115863577B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and in particular to a modified silicon-carbon negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in mobile phones, computers, small electric equipment, new energy vehicles and other industries due to their high energy density, high operating voltage and excellent cycle performance.
[0003] Silicon has a high theoretical specific capacity (4200mAh / g) and high energy density, and will gradually become the next generation of commercial negative electrode materials for lithium-ion batteries. However, as a negative electrode active material for lithium-ion batteries, after being fully embedded in Li+, the volume expansion reaches 300%. The pulverization and structural collapse produced during the charge and discharge process seriously affect its coulombic efficiency and capacity retention rate. The coating method, which is currently the mainstream modification method, is to use silicon-based materials as the core and wrap the outer layer with materials with low expansion properties to form a core-shell structure, which can effectively alleviate the volume expansion of silicon materials. Common coating methods include liquid phase coating, solid phase coating, and vapor phase deposition. Among them, the use of asphalt precursors and solid phase coating is widely accepted due to its simple process advantages. However, during the solid phase mixing process of silicon and asphalt, due to the low binding force, uneven dispersion at room temperature, and low fluidity, the prepared silicon-carbon material has poor coating uniformity, cannot form a stable SEI film, and the phenomenon of asphalt carbonized particles existing alone in the composite system, resulting in low capacity of electrode materials and other problems, affecting the initial charge and discharge capacity and coulombic efficiency of subsequent lithium-ion batteries. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a modified silicon-carbon negative electrode material and a preparation method thereof, which can effectively solve the problems of poor uniformity of carbon layer coating and particle adhesion and agglomeration, and realize a silicon-carbon composite material uniformly coated with asphalt solid phase. The negative electrode material can improve the capacity and initial efficiency of the silicon-carbon negative electrode.
[0005] In order to achieve the above technical effects, the present invention adopts the following technical solutions:
[0006] A method for preparing a modified silicon-carbon negative electrode material comprises the following steps: (1) mixing a modifier 2 with asphalt and stirring the mixture evenly, followed by carbonization treatment, cooling, crushing and screening to obtain a modified asphalt A; dynamically adding the modified asphalt A to a solution containing a modifier 1, dispersing the mixture through high-speed shearing in an emulsifier, heating, drying and crushing to obtain a modified asphalt B; (2) mixing a silicon source with a base carbon material to obtain a composite material C, and fully mixing the composite material C with the modified asphalt B at room temperature to obtain a silicon-carbon coated precursor material; and (3) calcining the silicon-carbon coated precursor material under inert atmosphere protection to obtain a Si / Gr@C composite material, and crushing and screening to obtain a modified silicon-carbon negative electrode material.
[0007] A further technical solution is that the asphalt in step (1) is coal asphalt or petroleum asphalt.
[0008] A further technical solution is that the general structural formula of the modifier 1 in step (1) is Where R is C 10 ~C 22 Alkyl, R' is methyl or C2~C4 alkyl or benzyl, and X is a counter ion halogen.
[0009] A further technical solution is that the modifier 2 in step (1) is selected from any one or more of polydimethylsiloxane, polyether block copolymer modified silicone oil, alkyl and polyether co-modified silicone oil, alkyl ether polyether silicone oil, epoxy polyether silicone oil, amino polyether block silicone oil, glycerol ether silicone oil, phosphate silicone oil, sugar polyether silicone oil, and betaine silicone oil.
[0010] A further technical solution is that the concentration of the modifier 1 solution in step (1) is 2-5%, and the mass ratio of the modifier 1 solution to the modified asphalt A is (1-2):1.
[0011] A further technical solution is that the mass ratio of the modifier 2 to the asphalt in step (1) is (0.2-1):1.
[0012] A further technical solution is that in step (1), the stirring temperature is 80-200° C., the carbonization treatment temperature is 350-500° C., and the time is 1-3 hours.
[0013] A further technical solution is that the base carbon material in step (2) is natural graphite, artificial graphite or mesophase carbon microbeads.
[0014] A further technical solution is that the silicon source in step (2) is commercially available gas-phase nano-silicon with a particle size of 80-200 nm, the particle size of the base carbon material is 5-20 μm, and the mass percentage of the silicon source in the base carbon material is 5-20%wt.
[0015] A further technical solution is that the mass ratio of the modified asphalt B in step (2) to the composite material C is 5 to 20%wt.
[0016] A further technical solution is that the calcination in step (3) is specifically carried out under the protection of an inert atmosphere, with a heating rate of 2 to 20°C / min, a carbonization temperature of 800 to 1200°C, and a high temperature insulation time of 1 to 3h.
[0017] The present invention provides a modified silicon-carbon negative electrode. The modified silicon-carbon negative electrode material structure is a core-shell structure in which a new glassy carbon material structure is formed after carbonization of asphalt and a modifier and is wrapped on the surface of a Si / Gr composite material. The modified silicon-carbon negative electrode is prepared by the above-mentioned preparation method.
[0018] The present invention also provides a lithium ion battery, which comprises the modified silicon-carbon negative electrode material.
[0019] The present invention is based on the fact that asphalt and silicon belong to a two-phase system with poor adsorption. Therefore, the present invention introduces a linear polysiloxane additive. After carbonization treatment, Si-C doped modified asphalt A is formed. On the basis of the outer shell forming a protective layer for the inner core, the capacity and first effect of the silicon-carbon negative electrode can be improved at the same time. Since the surface of the nano-silicon obtained by sand milling will produce hydroxyl functional groups and silicon oxide, etc., it will show a negative charge effect. The introduction of cationic additives with lipophilic groups can be adsorbed on the surface of nano-silicon and can be easily combined with asphalt, thereby increasing the adsorption strength of asphalt and nano-silicon surface and improving the continuity and uniformity of the coating layer. The present invention uses asphalt as a carbon material precursor, and selects fatty alkyl trimethylamine halides and linear polysiloxane additives. After modifying the asphalt, a silicon-carbon negative electrode active material with a narrow particle size distribution, a smooth particle surface, a uniform carbon layer coating, and a high capacity and first effect can be prepared.
[0020] Compared with the prior art, the present invention has the following beneficial effects: adding linear polysiloxane additives increases the affinity of asphalt with silicon source at low temperature, improves the dispersion effect of asphalt during solid mixing, and improves the capacity and cycle performance of silicon-carbon negative electrode materials. Adding fatty alkyl trimethylamine halide additives can increase the binding force between nano-silicon and liquid asphalt, improve the coating effect of silicon-carbon, and improve the uniformity of silicon-carbon negative electrode active material particles, the smoothness of coated particles, and the charge-discharge cycle performance. Compared with other processes, this method is simple to operate, has low modification and coating costs, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a test flow chart of the present invention;
[0022] Figure 2 This is a structural diagram of modified silicon-carbon negative electrode material;
[0023] Figure 3This is a scanning electron microscope image of the finished product of Example 1. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned feature requirements, objectives and beneficial effects of the present invention easier to understand, the specific implementation methods of the present invention are described in detail below in conjunction with implementation cases.
[0025] Example 1
[0026] Step 1: Weigh 100g of medium-temperature coal tar, heat to 150°C, add 20g of dimethylsiloxane, stir at 300rpm for 0.5h, place in a tubular furnace, heat to 500°C at 5°C / min, carbonize for 2h, cool and crush to obtain modified asphalt A; weigh 50g of modified asphalt A and add it to 2% hexadecyltrimethylammonium bromide solution (50g), after shear dispersion in an emulsifier, heat in an oil bath to 130°C to remove moisture, put in a 100°C vacuum oven to dry for 12h, crush to 20-60um to obtain modified asphalt B for use.
[0027] Step 2: Weigh 15g of nano-silicon and 85g of graphite, mix them to obtain composite material C; stir and mix them evenly with modified asphalt B (20g) obtained in step 1 at room temperature to obtain a silicon-carbon coated precursor material, place it in a tubular furnace, heat it to 800°C at a rate of 2°C / min, keep it warm for 1h, cool it naturally, crush it, and sieve it to obtain a modified silicon-carbon negative electrode active material.
[0028] The obtained active material particles D 50 Particle size is 16um, D max The particle size is 34um, the overall particle size concentration is high, and the specific surface area is 1.95m 2 / g.
[0029] Example 2
[0030] Step 1: Weigh 100g of medium-temperature coal tar, heat to 150°C, add 20g of glycosyl polyether silicone oil, stir at 300rpm for 0.5h, place in a tubular furnace, heat to 500°C at 5°C / min, carbonize for 2h, cool and crush to obtain modified asphalt A; weigh 50g of modified asphalt A and add it to 2% octadecyltrimethylammonium chloride solution (50g), after shear dispersion by emulsifier, heat to 130°C in an oil bath to remove moisture, put into a 100°C vacuum oven to dry for 12h, crush to 20-60um to obtain modified asphalt B for use.
[0031] Step 2: Weigh 15g of nano-silicon and 85g of graphite, mix them to obtain composite material C; stir and mix them evenly with modified asphalt B (20g) obtained in step 1 at room temperature to obtain a silicon-carbon coated precursor material, place it in a tubular furnace, heat it to 800°C at a rate of 2°C / min, keep it warm for 1h, cool it naturally, crush it, and sieve it to obtain a modified silicon-carbon negative electrode active material.
[0032] The obtained active material particles D 50 Particle size is 15um, D max The particle size is 33um, the overall particle size concentration is high, and the specific surface area is 2.03m 2 / g.
[0033] Example 3
[0034] Step 1: Weigh 100g of medium-temperature coal tar, heat to 150℃, add 20g of betaine-based silicone oil, stir at 300rpm for 0.5h, place in a tubular furnace, heat to 500℃ at 5℃ / min, carbonize for 2h, cool and crush to obtain modified asphalt A; weigh 50g of modified asphalt A and add it to 2% tetradecyltrimethylammonium bromide solution (50g), after shear dispersion in an emulsifier, heat in an oil bath to 130℃ to remove moisture, put in a 100℃ vacuum oven to dry for 12h, crush to 20-60um to obtain modified asphalt B for use.
[0035] Step 2: Weigh 15g of nano-silicon and 85g of graphite, mix them to obtain composite material C; stir and mix them evenly with modified asphalt B (20g) obtained in step 1 at room temperature to obtain a silicon-carbon coated precursor material, place it in a tubular furnace, heat it to 800°C at a rate of 2°C / min, keep it warm for 1h, cool it naturally, crush it, and sieve it to obtain a modified silicon-carbon negative electrode active material.
[0036] The obtained active material particles D 50 Particle size is 14um, D max The particle size is 32um, the overall particle size concentration is high, and the specific surface area is 1.89m 2 / g.
[0037] Example 4
[0038] Step 1: Weigh 100g of high-temperature coal tar, heat to 200℃, add 20g of betaine-based silicone oil, stir at 300rpm for 0.5h, place in a tubular furnace, heat to 500℃ at 5℃ / min, carbonize for 2h, cool and crush to obtain modified asphalt A; weigh 50g of modified asphalt A and add it to 2% tetradecyltrimethylammonium bromide solution (50g), after shear dispersion by emulsifier, heat to 130℃ in an oil bath to remove moisture, put into a 100℃ vacuum oven to dry for 12h, crush to 20-60um to obtain modified asphalt B for use.
[0039] Step 2: Weigh 15g of nano-silicon and 85g of graphite, mix them to obtain composite material C; stir and mix them evenly with modified asphalt B (5g) obtained in step 1 at room temperature to obtain a silicon-carbon coated precursor material, place it in a tubular furnace, heat it to 800°C at a rate of 5°C / min, keep it warm for 1h, cool it naturally, crush it, and sieve it to obtain a modified silicon-carbon negative electrode active material.
[0040] The obtained active material particles D 50 Particle size is 17um, D max The particle size is 34um, the overall particle size concentration is high, and the specific surface area is 2.4m 2 / g.
[0041] Example 5
[0042] Step 1: Weigh 100g of high-temperature coal tar, heat to 200℃, add 20g of betaine-based silicone oil and 30g of polydimethylsiloxane, stir at 300rpm for 0.5h, place in a tubular furnace, heat to 500℃ at 5℃ / min, carbonize for 3h, cool and crush to obtain modified asphalt A; weigh 50g of modified asphalt A and add it to 2% tetradecyltrimethylammonium bromide solution (50g), after shear dispersion in an emulsifier, heat in an oil bath to 130℃ to remove moisture, put in a 100℃ vacuum oven to dry for 12h, crush to 20-60um to obtain modified asphalt B for use.
[0043] Step 2: Weigh 5g of nano-silicon and 95g of mesophase carbon microspheres, mix them to obtain composite material C; stir and mix them evenly with modified asphalt B (5g) obtained in step 1 at room temperature to obtain a silicon-carbon coated precursor material, place it in a tubular furnace, heat it to 800°C at a rate of 5°C / min, keep it warm for 1h, cool it naturally, crush it, and sieve it to obtain a modified silicon-carbon negative electrode active material.
[0044] The obtained active material particles D 50 Particle size is 15um, D max The particle size is 29um, the overall particle size concentration is high, and the specific surface area is 2.24m 2 / g.
[0045] Example 6
[0046] Step 1: Weigh 100g of high-temperature coal tar, heat to 200℃, add 20g of betaine-based silicone oil and 30g of polydimethylsiloxane, stir at 300rpm for 0.5h, place in a tubular furnace, heat to 500℃ at 5℃ / min, carbonize for 3h, cool and crush to obtain modified asphalt A; weigh 50g of modified asphalt A and add it to 2% tetradecyltrimethylammonium bromide solution (50g), after shear dispersion in an emulsifier, heat in an oil bath to 130℃ to remove moisture, put in a 100℃ vacuum oven to dry for 12h, crush to 20-60um to obtain modified asphalt B for use.
[0047] Step 2: Weigh 5g of nano-silicon and 95g of mesophase carbon microspheres, mix them to obtain composite material C; stir and mix them evenly with modified asphalt B (5g) obtained in step 1 at room temperature to obtain a silicon-carbon coated precursor material, place it in a tubular furnace, heat it to 1200°C at a rate of 5°C / min, keep it warm for 3h, cool it naturally, crush it, and sieve it to obtain a modified silicon-carbon negative electrode active material.
[0048] The obtained active material particles D 50 Particle size is 17um, D max The particle size is 33um, the overall particle size concentration is high, and the specific surface area is 2.19m 2 / g.
[0049] Example 7
[0050] Step 1: Weigh 100g of petroleum asphalt, heat to 80℃, add 20g of betaine-based silicone oil, stir at 300rpm for 0.5h, place in a tubular furnace, heat to 350℃ at 5℃ / min, carbonize for 3h, cool and crush to obtain modified asphalt A; weigh 50g of modified asphalt A and add it to 5% tetradecyltrimethylammonium bromide solution (50g), after shear dispersion in an emulsifier, heat in an oil bath to 130℃ to remove moisture, put in a 100℃ vacuum oven to dry for 12h, crush to 20-60um to obtain modified asphalt B for use.
[0051] Step 2: Weigh 5g of nano-silicon and 95g of mesophase carbon microspheres, mix them to obtain composite material C; stir and mix them evenly with modified asphalt B (5g) obtained in step 1 at room temperature to obtain a silicon-carbon coated precursor material, place it in a tubular furnace, heat it to 1200°C at a rate of 20°C / min, keep it warm for 3h, cool it naturally, crush it, and sieve it to obtain a modified silicon-carbon negative electrode active material.
[0052] The obtained active material particles D 50 Particle size is 16um, D max The particle size is 36um, the overall particle size concentration is high, and the specific surface area is 1.94m 2 / g.
[0053] Example 8
[0054] Step 1: Weigh 100g of medium-temperature coal tar, heat to 150℃, add 20g of betaine-based silicone oil, stir at 300rpm for 0.5h, place in a tubular furnace, heat to 350℃ at 5℃ / min, carbonize for 3h, cool and crush to obtain modified asphalt A; weigh 50g of modified asphalt A and add it to 2% tetradecyltrimethylammonium bromide solution (100g), after shear dispersion in an emulsifier, heat in an oil bath to 130℃ to remove moisture, put in a 100℃ vacuum oven to dry for 12h, crush to 20-60um to obtain modified asphalt B for use.
[0055] Step 2: Weigh 5g of nano-silicon and 95g of mesophase carbon microspheres, mix them to obtain composite material C; stir and mix them evenly with modified asphalt B (5g) obtained in step 1 at room temperature to obtain a silicon-carbon coated precursor material, place it in a tubular furnace, heat it to 1200°C at a rate of 5°C / min, keep it warm for 1h, cool it naturally, crush it, and sieve it to obtain a modified silicon-carbon negative electrode active material.
[0056] The obtained active material particles D 50 Particle size is 12um, D max The particle size is 35um, the overall particle size concentration is high, and the specific surface area is 2.05m 2 / g.
[0057] Example 9
[0058] Step 1: Weigh 100g of medium-temperature coal tar, heat to 150℃, add 20g of betaine-based silicone oil, stir at 300rpm for 0.5h, place in a tubular furnace, heat to 350℃ at 5℃ / min, carbonize for 3h, cool and crush to obtain modified asphalt A; weigh 50g of modified asphalt A and add it to 2% tetradecyltrimethylammonium bromide solution (100g), after shear dispersion in an emulsifier, heat in an oil bath to 130℃ to remove moisture, put in a 100℃ vacuum oven to dry for 12h, crush to 20-60um to obtain modified asphalt B for use.
[0059] Step 2: Weigh 5g of nano-silicon and 95g of natural graphite, mix them to obtain composite material C; stir and mix them evenly with modified asphalt B (5g) obtained in step 1 at room temperature to obtain a silicon-carbon coated precursor material, place it in a tubular furnace, heat it to 1200°C at a rate of 5°C / min, keep it warm for 1h, cool it naturally, crush it, and sieve it to obtain a modified silicon-carbon negative electrode active material.
[0060] The obtained active material particles D 50 Particle size is 19um, D max The particle size is 38um, the overall particle size concentration is high, and the specific surface area is 2.15m 2 / g.
[0061] Comparative Example 1
[0062] The preparation process is the same as that of the above implementation case 1, except that no additives are added to pre-treat the asphalt.
[0063] The obtained active material particles D 50 Particle size is 21um, D max The particle size is 45um, the overall particle size is relatively large, and the specific surface area is 1.4m 2 / g.
[0064] The modified silicon-carbon active material prepared by the above implementation case was used to make a negative electrode sheet with a ratio of active material: carbon black: binder of 8:1:1, and assembled into a half-cell to test its electrochemical performance. The test results are shown in the following table:
[0065] Table 1 Comparison of charging and discharging performance of button half-cells in implementation cases
[0066]
[0067]
[0068] From the above cases, we can see that after the introduction of additive-modified asphalt, the particle size of the finished product particles is reduced, indicating that the granulation improvement effect is obvious, the finished product has a smooth microstructure, and the coating effect is greatly improved. During the charging and discharging process, the direct contact between the electrolyte and silicon is hindered, which effectively improves the first coulombic efficiency and cycle capacity retention rate of the finished product.
[0069] Although the present invention is described herein with reference to the illustrative embodiments of the present invention, the above embodiments are only preferred embodiments of the present invention, and the embodiments of the present invention are not limited to the above embodiments. It should be understood that those skilled in the art can design many other modifications and embodiments, which will fall within the scope and spirit of the principles disclosed in this application.
Claims
1. A method for preparing a modified silicon-carbon negative electrode material, It is characterized in that The method comprises the following steps: (1) mixing modifier 2 with asphalt and stirring the mixture evenly, then carbonizing the mixture, cooling, crushing and screening the mixture to obtain modified asphalt A; wherein the modifier 2 in step (1) is selected from any one or more of polydimethylsiloxane, polyether block copolymer modified silicone oil, alkyl and polyether co-modified silicone oil, alkyl ether polyether silicone oil, epoxy polyether silicone oil, amino polyether block silicone oil, glycerol ether silicone oil, phosphate silicone oil, sugar polyether silicone oil and betaine silicone oil; and dynamically adding modified asphalt A to a solution containing modifier 1, dispersing the mixture through high-speed shearing in an emulsifier, heating and drying the mixture and crushing the mixture to obtain modified asphalt B; wherein the general structural formula of the modifier 1 in step (1) is Where R is C 10 ~C 22 Alkyl, R' is methyl or C 2 ~C 4 Alkyl or benzyl, X is a counter ion halogen; (2) mixing a silicon source with a base carbon material to obtain a composite material C, and fully mixing the composite material C with a modified asphalt B at room temperature to obtain a silicon-carbon coated precursor material; (3) calcining the silicon-carbon coated precursor material under an inert atmosphere to obtain a Si / Gr@C composite material, and after crushing and screening, obtaining a modified silicon-carbon negative electrode material.
2. The method for preparing the modified silicon-carbon negative electrode material according to claim 1, It is characterized in that The asphalt in step (1) is coal asphalt or petroleum asphalt.
3. The method for preparing the modified silicon-carbon negative electrode material according to claim 1, It is characterized in that The concentration of the modifier 1 solution in step (1) is 2-5%, and the mass ratio of the modifier 1 solution to the modified asphalt A is (1-2):
1.
4. The method for preparing the modified silicon-carbon negative electrode material according to claim 1, It is characterized in that The mass ratio of the modifier 2 to the asphalt in step (1) is (0.2-1):
1.
5. The method for preparing the modified silicon-carbon negative electrode material according to claim 1, It is characterized in that In step (1), the stirring temperature is 80-200° C., the carbonization treatment temperature is 350-500° C., and the time is 1-3 hours.
6. The method for preparing the modified silicon-carbon negative electrode material according to claim 1, It is characterized in that The base carbon material in step (2) is natural graphite, artificial graphite or mesophase carbon microspheres.
7. The method for preparing the modified silicon-carbon negative electrode material according to claim 1, It is characterized in that The silicon source in step (2) is commercially available gas-phase nano-silicon with a particle size of 80-200 nm, the particle size of the base carbon material is 5-20 μm, and the mass percentage of the silicon source in the base carbon material is 5-20%wt.
8. The method for preparing the modified silicon-carbon negative electrode material according to claim 1, It is characterized in that In step (2), the mass ratio of the modified asphalt B to the composite material C is 5-20%wt.
9. The method for preparing the modified silicon-carbon negative electrode material according to claim 1, It is characterized in that The calcination in step (3) is specifically carried out under the protection of an inert atmosphere, with a heating rate of 2 to 20° C. / min, a carbonization temperature of 800 to 1200° C., and a high temperature insulation time of 1 to 3 hours.
10. A modified silicon-carbon negative electrode material, It is characterized in that The modified silicon-carbon negative electrode material structure is a core-shell structure in which a new glassy carbon material structure is formed after carbonization of asphalt and a modifier and is wrapped on the surface of a Si / Gr composite material. It is prepared by the preparation method described in any one of claims 1-9.
11. A lithium ion battery, It is characterized in that The lithium-ion battery comprises the modified silicon-carbon negative electrode material according to claim 10.
Citation Information
Cited By
Process for preparing silicon-carbon negative electrode material by emulsification method and silicon-carbon negative electrode material
CN116854074A
Process for preparing silicon-carbon negative electrode material by emulsification method and silicon-carbon negative electrode material
CN116854074B
Preparation process of carbon-silicon coated negative electrode material
CN120039879A
